Optimalisasi Sistem Perawatan dan Perbaikan Mesin Vertical Mill di PT. Semen Padang - Wahmin Rais; Afrizul Evendi; Adriansyah Adriansyah; Darman Dapersal Dinar (Jurnal Teknik Mesin, 2020)
Vertical Mill is one of the main equipment in the Indarung IV factory PT. Semen Padang. This Vertical Mill is used to grind / crush the main ingredients of making cement such as Limestone, Silica stone, Clay, and Iron sand. Milling of this material is done with the help of a tool called a Roller Tire and grinding table. So that the Tire Tire and grinding table always work as expected, the Roller Tire and grinding table must be maintained and repaired continuously and planned. Major damage that is often encountered is the occurrence of wear and tear on the Tire Roller and the grinding roller. Countermeasures by adding meat to the Tire Roller and grinding table using welding. With the maintenance and repairs are well scheduled, then we can avoid the causes of a damage from the beginning.